2011
DOI: 10.1186/1479-5868-8-135
|View full text |Cite
|
Sign up to set email alerts
|

Calorie menu labeling on quick-service restaurant menus: an updated systematic review of the literature

Abstract: Nutrition labels are one strategy being used to combat the increasing prevalence of overweight and obesity in the United States. The Patient Protection and Affordable Care Act of 2010 mandates that calorie labels be added to menu boards of chain restaurants with 20 or more locations. This systematic review includes seven studies published since the last review on the topic in 2008. Authors searched for peer-reviewed studies using PUBMED and Google Scholar. Included studies used an experimental or quasi-experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
183
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(193 citation statements)
references
References 20 publications
9
183
0
1
Order By: Relevance
“…This will reduce situations where establishments have to meet many different menu-labeling requirements because of varying state and local regulations. The FDA rule may also cover some establishments that may not have been covered under some state laws.Numerous studies (and several systematic reviews) have previously tried to assess the effects of local labeling rules, but the results have been mixed and sometimes contradictory (VanEpps et al, 2016;Sarink et al, 2016;Long et al, 2015;Sinclair, Cooper, and Mansfield, 2014;Swartz, Braxton, and Viera, 2011). There are plausible reasons for these different findings, including study design elements like sample size and varying types of labels (e.g., calories alone versus contextual), the restaurant setting in which the study took place, and types of customers.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This will reduce situations where establishments have to meet many different menu-labeling requirements because of varying state and local regulations. The FDA rule may also cover some establishments that may not have been covered under some state laws.Numerous studies (and several systematic reviews) have previously tried to assess the effects of local labeling rules, but the results have been mixed and sometimes contradictory (VanEpps et al, 2016;Sarink et al, 2016;Long et al, 2015;Sinclair, Cooper, and Mansfield, 2014;Swartz, Braxton, and Viera, 2011). There are plausible reasons for these different findings, including study design elements like sample size and varying types of labels (e.g., calories alone versus contextual), the restaurant setting in which the study took place, and types of customers.…”
mentioning
confidence: 89%
“…Numerous studies (and several systematic reviews) have tried to assess the effects of local menu labeling rules, but the results of the reviews have been mixed and sometimes contradictory (VanEpps et al, 2016;Sarink et al, 2016;Long et al, 2015;Sinclair, Cooper, and Mansfield, 2014;Swartz, Braxton, and Viera, 2011). There are plausible reasons for this heterogeneity, such as differences in label styles and information provided, differences in the types of restaurants in the study, and variance in groups of participants.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Nutrition information OH allows consumers to make a more informed dietary choice and is a strategy highlighted in half the policies targeting the OH eating sector, making it the most frequently used strategy for promoting healthier food options OH. While it is imperative that consumers have the necessary information to make informed decisions when eating OH, research on the influence of menu labelling has found that any beneficial effect is limited (96)(97)(98) . The Swartz et al (97) review on the effect of menu labelling recommended that caterers' response to menu labelling regulations should be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…While it is imperative that consumers have the necessary information to make informed decisions when eating OH, research on the influence of menu labelling has found that any beneficial effect is limited (96)(97)(98) . The Swartz et al (97) review on the effect of menu labelling recommended that caterers' response to menu labelling regulations should be monitored. A 2-year study in New York City found that some restaurants introduced new menu items with lower energy contents following mandating of energy labelling and in these establishments consumers' purchases decreased in energy content; however, this was not a main outcome measure of this study (99) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review identified surprisingly few studies about menu labeling and food intake. 3 This review 3 concluded that 'ycalorie menu labeling does not have the intended effect of decreasing calorie ordering and consumption from quick-service restaurants'. Girz et al 2 now add information about food selection and intake by restrained and unrestrained eaters, when calorie information is provided about salad and pasta, which are traditionally perceived to be healthful vs high-calorie foods.…”
mentioning
confidence: 99%